2020
DOI: 10.1007/s40843-020-1471-0
|View full text |Cite
|
Sign up to set email alerts
|

High and selective capture of low-concentration CO2 with an anion-functionalized ultramicroporous metal-organic framework

Abstract: CO 2 capture, especially under low-pressure range, is of significance to maintain long-duration human operation in confined spaces and decrease the CO 2 corrosion and freezing effect for the liquefaction of natural gas. Herein, we for the first time report a novel anion-functionalized ZU-16-Co (TIFSIX-3-Co, TIFSIX=hexafluorotitanate (TiF 6 2−), 3=pyrazine), which exhibits one-dimensional pore channels decorated by abundant F atoms, for efficient CO 2 capture at a concentration around 400-10,000 ppm. Among its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 42 publications
(46 reference statements)
0
22
0
Order By: Relevance
“…Zhang et al 106 reported a novel anion-functionalized ZU16-Co (TIFSIX-3-Co) that could effectively capture CO 2 at a concentration of about 400–10 000 ppm. The CO 2 adsorption capacity at 298 K, 1 bar is 2.87 mmol g −1 , and the separation selectivity for CO 2 /N 2 (15/85) is 690.…”
Section: Modification Methods Of Mofs For Co2 Capturementioning
confidence: 99%
“…Zhang et al 106 reported a novel anion-functionalized ZU16-Co (TIFSIX-3-Co) that could effectively capture CO 2 at a concentration of about 400–10 000 ppm. The CO 2 adsorption capacity at 298 K, 1 bar is 2.87 mmol g −1 , and the separation selectivity for CO 2 /N 2 (15/85) is 690.…”
Section: Modification Methods Of Mofs For Co2 Capturementioning
confidence: 99%
“…The uptake capacity on the functionalized MOF was however slightly lower as compared to other high-performing MOFs such as TIFSIX-3-Ni (∼1.1 mmol g −1 at 298 K) 31 and ZU-16-Co (∼1.05 mmol g −1 at 298 K). 53 Correspondingly, the Δ H ads of the pyrazine-functionalized Co-MOF-74 was higher (−48.4 kJ mol −1 at zero loading) than other frameworks with highly tailored pore structures ( e.g. NbOFFIVE-1-Ni, −54.9 kJ mol −1 at 0.1 mmol g −1 CO 2 loading) 47 or chemisorption-based sorbents ( e.g.…”
Section: Strategies For Enhancing Co2 Capture Performance On Mofsmentioning
confidence: 97%
“…In particular, some MOFs with excellent performance are sensitive to water because of the weak bonding mode of coordination bonds, which greatly limits CO 2 capture by MOFs. 39,40…”
Section: Introductionmentioning
confidence: 99%